Effectiveness of and Access to Medications for Opioid Use Disorder for Adolescents and Young Adults: A Scoping Review. Issue 3 (May 2022) - McCarty, Dennis; Chan, Brian; Buchheit, Bradley M.; Bougatsos, Christina; Grusing, Sara; Chou, Roger
Abstract : Objective: A scoping review assessed access to medications for opioid use disorder (MOUD) and treatment outcomes among adolescents (12 – 17 years) and young adults (18 – 25 years). Methods: Studies addressing adolescent and young adult opioid use disorder and treatment with MOUD on patient outcomes (eg, retention in care) were included. Randomized trials and controlled observational studies were prioritized. Investigators extracted key information, summarized findings, noted methodological weaknesses, and tabled the details. Results: The search identified 4 randomized trials (N = 241), 1 systematic review with 52 studies (total N = 125, 994), and 5 retrospective analyses of health insurance claims. The trials reported buprenorphine and extended-release naltrexone reduced opioid use. Return to use was observed when pharmacotherapy ceased. A systematic review concluded that adolescents and young adults had lower retention in care than older adults. The observational studies found that adolescents were unlikely to receive MOUD. There was some evidence that non-Hispanic Black adolescents and young adults were less likely than non-Hispanic Whites to receive MOUD. Conclusions: MOUD therapies reduce opioid use among adolescent and young adults but few receive MOUD. MOUD services for adolescents and young adults should be developed and tested. Randomized clinical trials are necessary to develop appropriate clinical guidelines for using MOUD with adolescents and young adults.